Az államháztartási számvitel szabályozás változása a Csornai Margit Kórház példáján keresztül - Kovácsné Horváth Mária (2016)
My topic selection was justified first of all by the fact that from January 01, 2014 a signif-icant change has come to effect for the first time for a long time among the figures of budget regarding accountancy. The regulation system with an approach of cash flow was replaced by an accounting system with an approach of cash flow and result. The main objective of my essay is to introduce the new accounting rules related to the figures of public accounts and to compare them with the old accounting rules on the one hand in relation with the balance and on the other hand in the other parts of the budget report through the example of the Margit Hospital in Csorna. First I have introduced the brief history and the organization of the Margit Hospital of Csorna. Then I have stated the purpose and main regulations of the executive decree about the Budget accountancy. I have introduced the method of book-keeping, the budget accountancy, financial accountancy, the application of financial principles and the set-up of the budget report required by the new measure. I have demonstrated the modification of balance and the reclassification regarding balance modification in the institute. I have particularly presented the manual, reclassification and book-keeping technical tasks, the performance of which has become unconditionally necessary after the preparation of the statement of the year 2013, in order to be able to switch. In my essay I have prepared the report of the Margit Hospital of Csorna for the year 2014 also according to the accounting rules of the year 2013. Through this the changes has become comparable not only regard-ing their content, but also regarding the amounts. The conformities and differences prior to and after the change could be observed. The individual changes have concerned only the reclassification of certain balance items between each other, namely only the values of the balance positions have been changed, however these corrections did not result any change in the balance sheet total. The other part of the changes has affected also the balance sheet total as well, both regarding assets and sources. So these changes have resulted also modi-fication of the assets of the hospital. In case of the reporting tables to be prepared addi-tional to the balance I have only carried out content comparisons to investigate conformi-ties and differences. In the aggregate it can be stated that the modifications have resulted a change typi-cally in single items of the balance. The modification of assets is resulting first of all from the introduction of the recording of accrued and deferred items. The preparation of the annual budget report has become significantly simply upon the effect of these modifica-tions, simultaneously regarding its content it complies both with the data supply require-ments of the budget and the European Community.